Bergapten alleviates senescence of chondrocytes in osteoarthritis - YE Yuanlan; LIU Kaiwen; PAN Yiming (陆军军医大学学报)
Objective‍　‍To investigate the role and mechanism of bergapten in treating osteoarthritis (OA) based on network pharmacology, molecular docking and in vitro experiments. Methods‍　‍The functional targets of bergapten and the related targets of OA disease were obtained by searching Super-Pred， Swiss Target Prediction， Drug Bank. The obtained targets were intersected with Venny2.1.0, protein-protein interaction (PPI) analysis was performed using the STRING database, and molecular docking was conducted by AutoDock Vina. Subsequently, human chondrocyte C28/I2 cells were subjected in the following validation experiments. After the cells were treated with 0~50 μmol/L bergapten for 24, 48 or 72 h, CCK-8 assay, RT-qPCR and immunofluorescence assay were used to detect the proliferation and apoptosis, and the expression of the molecules related to proliferation, inflammation and senescence (senescence associated secretory phenotype, SASP). Senescence β-galactosidase (SA-β-Gal) staining kit was employed to detect the change of SA-β-Gal level in the cells. Results‍　‍There obtained 145 potential targets of bergapten for OA. PPI analysis revealed 4 potential core targets, HSP90AA1, EGFR, HIF1A, and PIK3CA, and they could form relatively stable complex with bergapten. CCK-8 assay showed that 10 μmol/L bergapten treatment for 48 h resulted in the highest proliferative activity of C28/I2 cells (P<0.05). Immunofluorescence assay, RT-qPCR and Western blotting indicated that bergapten treatment induced significant increases in the expression of cell proliferation markers such as PCNA, CCND1 and CCNE1 (P<0.05), while decreases in the expression of apoptosis markers Caspase3 and BAX (P<0.05). Meanwhile, the expression levels of IL-1β-induced inflammatory factors IL-6 and TNF-α were reduced, while those of anti-inflammatory factors IL-4 and IL-10 were elevated after bergapten treatment (P<0.05). The levels of SASP factors, such as P16, P21, MMP9 and MMP13 were also significantly declined (P<0.05). SA-β-Gal staining displayed that the level of SA-β-Gal in C28/I2 cells was significantly enhanced after IL-1β induction (P<0.05), while bergapten treatment could decrease the positive cell rate of the staining (P<0.05). Conclusion‍　‍Bergapten can reduce the expression of SASP factors such as IL-6, TNF-α, P16, P21, MMP9 and MMP13 in IL-1β-stimulated chondrocytes, and thus exerts its anti-inflammatory and anti-aging effects in delaying the progression of OA.